Adaptive Educational Governance for Economic Sustainability: China’s Policy Innovations in Response to Demographic Aging - HU, MINGQI; SENAWI, AZHAN RASHID (Journal of Ecohumanism, 2024)
Through a combination of quantitative and qualitative analyses, this study examines how China can respond to the challenges of population ageing and maintain sustainable economic development through innovative education management policies. The study first presents the dynamic trends of population ageing in China and its multidimensional impact on economic and social development using descriptive statistics and time series analysis. The study then analyses the key role of adaptive education management in addressing this challenge by constructing an econometric model. This paper proposes an innovative conceptual framework of "Adaptive Educational Management for Economic Sustainability" and verifies its validity through empirical analyses. The study adopts a mixed research methodology at , combining panel data analysis and multi-case comparative studies to systematically assess China’s policy practices in this area in recent years. The study finds that measures such as implementing lifelong learning programmes, promoting the matching of gerontological education with industrial needs, and developing silver-hair economy-related professions have had a significant effect on alleviating the pressure of population ageing. However, the study also reveals problems such as regional imbalance in the implementation of current policies. Based on the research findings, this paper proposes a series of targeted policy recommendations and discusses the theoretical contributions of the framework and its implications for other countries facing similar challenges. This study not only provides data-supported policy ideas for China’s response to population ageing, but also provides valuable references for education reform and sustainable economic development in the context of global population ageing.